Photoelectrical characteristics of GaAs p-n junctions formed by Cu photostimulated diffusion - Dzhafarov, TD; Sirin, M; Akciz, S (IOP PUBLISHING LTD, 1998)
The influence of illumination of Cu-nGaAs structures by white light at room temperatures on the penetration of copper by diffusion into substrates and on electrical and photovoltaic characteristics of structures was investigated by using the energy dispersive x-ray fluorescence (XRF) technique, current-voltage measurements and measurements of the spectral distribution of the photosensitivity. The formation of a p-n junction in GaAs as a result of photostimulated diffusion of copper into GaAs was discovered. The prepared p-n photocells exhibited the parameters J(sc) = 1.3 mA cm(-2), V-oc = 315 mV and fill factor 0.35. The spectral distribution of the photosensitivity of cells extended from 660 to 880 nm. The mechanism for photostimulated diffusion of Cu into GaAs at room temperatures suggested is related to the influence of internal electric fields arising in the near-surface region of GaAs substrates under illumination.
Keywords: LIGHT-INDUCED REACTIVATION; METASTABLE STATE; ACCEPTORS; Physics